Pengaruh Perawatan Payudara terhadap Bendungan ASI pada Ibu Menyusui: Literature Review - Umayah Kumalasari; Tiara Permata Sari (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
According to WHO data from 2018, the average percentage of women experiencing breast engorgement during breastfeeding reached 87.06% or 8242 women. However, according to a study by the Indonesian Health Research and Development Agency in 2018, the highest incidence of breast engorgement in Indonesia occurred in working mothers, accounting for 6% of breastfeeding mothers. The aim of this literature review is to determine the extent of the influence of breast care on breast engorgement in breastfeeding mothers. This study utilizes a literature review method by collecting and analyzing 10 full-text Indonesian-language journals from 2019 to 2023 from sources available in databases such as Google Scholar using keywords such as breast engorgement, breast care, and breastfeeding. The inclusion criteria for this work are journals that investigate breastfeeding mothers undergoing breast care. Based on the keywords used, 10 journals that meet the criteria were found, and all of them indicate that breast care has an impact on breast engorgement. In the 10 journals reviewed, breast care is identified as one of the dominant factors in breast engorgement incidence because it can facilitate breast milk flow and reduce the likelihood of breast engorgement.